Pelatihan Inovasi Usaha dan Digital Marketing Bagi Pelaku Usaha Catering dan Angkringan di Kel. Sidanegara, Kec. Cilacap Tengah, Kab. Cilacap - Asharryadi Noegroho; Annisa Rahayu Pangesti; Dede Yusuf; Safitri Dwi Lestari; Syifa Marsyanda (Jurnal Pelayanan Masyarakat, 2024)
Business Innovation and Digital Marketing Literacy is important knowledge to improve business development and how to utilize digital marketing among society now and in the future. Good literacy knowledge of business innovation and digital marketing makes people who want to or have even entered the business world able to plan, manage and develop their business. Entrepreneurship is one way that can be done by various groups of people to gain social status in society, improve the community's economy and for investment in the future. The aim of this service is to improve the mindset of good, organized, innovative business development and more contemporary marketing, especially for MSMEs in the Cilacap Regency area. As a result of this activity, it is hoped that the public will gain knowledge regarding how to innovate business development and attractive digital marketing.